Effect of nonlinear material behavior on progressive failure analysis of pin-joint composites - Cayir, Sibel; Kaman, Mete Onur; Albayrak, Mustafa (Taylor & Francis Inc, 2024)
In this study, the mechanical performances of glass fiber-reinforced notched and pin-connected composite plates were investigated experimentally and numerically. For this purpose, composite plates with a circular hole, semicircular double-edge notched, U-edge notched, and single and double pin joints were prepared from [0 degrees]8 layer glass fiber composites. Tensile tests were carried out on the obtained specimens. The effect of notch type, number of pins, and position of pins on plate damage load and type was investigated for linear and non-linear material behavior. Progressive failure analysis was performed using the Hashin damage criteria. Subprogram codes were written in the Ansys program using the finite element method. According to the obtained data, it was determined that the type of notch and the number of pins have a significant effect on the damage loads of the plates and the behavior of the material is important in terms of convergence to the experimental results in numerical solutions. In single-pin composites, the type of damage changed from net-tension to shear out as the pin approached the free edge of the plate. It was observed that the distance between the pins did not have any effect on the damage type of the composites in the double-pin joint structure. Compared to single-pin joint composites, double-pin joint composites were found to carry a maximum of 34% more damage load. The convergence rate of experimental and numerical data was obtained as a minimum of 92.1% for nonlinear material behavior and a minimum of 73.4% for linear material behavior
Keywords: Laminated composite; nonlinear material; pin; progressive failure analysis